Metazoan ectoparasites of Lithognathus mormyrus (Linnaeus, 1758) from the western coast of Libya - Malak. T. Altikbali; Mohamed. L. Showehdi; Sarah A. Benzeglam; Aisha A. Seif-Alnaser; Esmail A. Shakman (Open Veterinary Journal, 2024)
Background: Lithognathus mormyrus fish is one of the fish of high economic importance in the countries of the world in general and the Mediterranean countries in specific, including the Libyan Sea waters, for this it is necessary to know everything related to this type of fish, including its infection with parasites. Parasites are considered one of the factors threatening the life of fish, being one of the food chains and the ecological composition of life. Aim: The current study aims to isolate and identify the parasites that infect the L. mormyrus. Methods: A total of 368 specimens of L. mormyrus were collected by fishermen, from the western coast of Libya. The study was focused on metazoan parasites. When fish were fully examined for the presence of ectoparasites under a dissecting microscope with incident light, the software camera connected with a microscope and semichon' acetocarmine technique for identification of parasites. Results: Two species of Monogenea (Encotyllabe valley, Pagellicotyle mormyri, and Lamellodiscus spp.), Isopoda (Gnathia), Copepoda (Lernaeolophus sultanus), and Annelidae (Trachelobdella lubrica) has been isolated from this species of fish. The highest prevalence of infection was Gnathia parasites (8.47%). Conclusion: There were differences in the parasite species that infect L. mormyrus from one country to another, and also from city to other cities in the same country, as in the Tunisian waters. [Open Vet J 2024; 14(8.000): 1771-1778]